Where,

a = Apothem Length

b = Length of Side

l = Slant Height

Where,

b = Base

l = Slant Height

Where,

V = Volume

H = Height between Bases

X = Length of Upper Rectangular Base

Y = Width of Upper Rectangular Base

x = Length of Lower Rectangular Base

y = Width of Lower Rectangular Base

Where,

V = Volume

H = Height between Bases

D = Diameter of the Upper Circular Base

d = Diameter of the Lower Circular Base

Height = v / (π × r

v = Volume

r= Radius

V = (h/3)×(a+b+√(a×b))

Where,

V = Volume

H = Altitude

A = Lower Base Area

B = Upper Base Area

Total Surface Area = (π × (A + B) × h) + (2 × π × A × B)

Where,

t = Total surface area

A= Semi Major Axis

B= Semi Minor Axis

h = Height

Lateral Surface Area = h × 2 × π × √((1/2) × ((A × A) + (B × B)))

Where,

h = Height

A = Semi Major axis

B = Semi Minor Axis

Curved surface area = π × H × (A + B)

Where,

H = Height

A = Semi-Major Axis

B = Semi-Minor Axis

Volume (V) = π × A × B × h

Where,

A = Semi-Major Axis

B = Semi-Minor Axis

h = Height

Surface Area (SA) = (2 × π × r × h) + ((π × r) × (r+ (√(c

Where,

r = Radius

h = Cylinder Height

c = Cone Height

Lateral Surface Area = π × 2 × r × h

Where,

r= Radius

h = Height

Volume (V) = (π ×r × r × h) + ((1/3) × (π × r × r × c))

Where,

r = Radius

c = Cone Height

h =Cylinder Height

Where,

r = Radius of Cone

v = Volume of Cone

h = Height of Cone

Where,

V = Volume of an Incomplete Pyramid

H = Height

A = Base Side

B = Top Side

Where,

d = Diagonal of Cube

a = Edge of Cube

Where,

C = Circumference Sphere

V = Volume of Sphere

Where,

CSA = Cross Section Area of Cube

L = Length of Cube

b = hl

c = wl

SA = 2[a + b + c]

V = hwl

Where,

h = Height of Box

l = Length of Box

w = Width of Box

SA = Total Surface Area of Box

V = Volume of Box

Where,

l = Triangle Height

b = Base Length

I = A × √(6) / 6

Where,

I = Insphere Radius

A = Edge Length

M = A / 2

Where,

M = Midsphere Radius

A = Edge Length

S = 3 × √(6) / A

Where,

S = Surface to Volume Ratio

A = Edge Length

D = √(2) × a

Where,

D = Diagonal

A = Edge Length

A = √(E/2/√3)

Where,

E = Surface Area

A = Edge Length

Where,

g = Center of Gravity

h = Height of Cone

Where,

b = Base Surface Area

a = Side length

Where,

a = Side Length

h = Height

v = Volume

Total Surface Area = a

Where,

a = Base

b = Truncated Base

h = Total Height